Comparison of anthropometric profile and cognitive performance of elite and non-elite beach volleyballaAthletes - Leite de Arruda, D. P.; Santos da Costa, A.; de Luna Ramalho Santos, A. K.; Paz, C. R.; Maroja Di Pace França, C. L.; de Lucena Barbosa, E.; Silva dos Santos, L.; de Araujo Leite Filho, M. A.; de Almeida, M. A. C.; Paz, M. H.; Netto Segundo, M. N.; Mariz Dantas, P. A.; et al. (IntechOpen, 2021)
To compare the anthropometric profile and cognitive performance of elite and non-elite beach volleyball athletes. Comparative and descriptive study. The sample was composed by 8 athletes, divided in 2 groups: elite (n = 4) and non-elite (n = 4). They were evaluated in anthropometric parameters age, weight and height, and the variables of the cognitive performance evaluated by the battery of computerized tests CogState® (Brief Battery): Detection (Simple Reaction Time); Identification (Choice Reaction Time); One Back Speed (Working Memory); One Back Acuracy (Short Term Memory). Data were classified as non-parametric with the dispersion curve analysis performed by the Shapiro Wilk test. Anthropometric profile and cognitive performance variables were compared with the Mann Whitney U test between the groups. The procedures were performed with a significance level of p < 0.05 using the Statistical Package for the Social Science - SPSS®, Version 25.0. It was observed that there was significant difference in the anthropometric profile in the variable age (sig = 0.029) and in the cognitive performance significant differences occurred in the variables Detec (sig = 0.029) and Indent (sig = 0.029) of elite and not elite athletes of the beach volleyball modality. Elite and non-elite beach volleyball athletes present significant differences in the anthropometric variable (Age) and in the variables of cognitive performance (Detection and Identification) where elite athletes have a better cognitive performance than the non- elite athletes.